PENGEMBANGAN MINUMAN FUNGSIONAL DARI EKSTRAK KULIT MUNDAR - Faizah Andarini; Sedarnawati Yasni; Elvira Syamsir (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Mundar or red mangosteen (Garcinia forbesii) peel has been known to contain various bioactive compounds with antioxidant potential, but research on its utilization is limited. The aim of this research was to utilize red mangosteen peel for producing a ready-to-drink beverage with superior antioxidant activity and good acceptance of its sensory. In this study, dried red mangosteen peel (moisture content of 12%) was extracted with water (1:3, 1:5, 1:7, and 1:10 w/v) at different temperatures (40 and 50°C). The antioxidant potentials of the extracts were compared in terms of their DPPH radical scavenging activities, total phenolic contents, and total monomeric anthocyanin contents. The red mangosteen peel extracted with water at a ratio of 1:7 at 40°C showed the highest antioxidant activity, i.e. 717.44±0.44 AAE µg/mL, 843.48±0.77 GAE µg/mL, and 46.55±0.30 CGE mg/L, respectively. These extracts were then mixed with corn milk, cinnamon extract and sucralose to develop functional beverages. Three beverage formulas with different concentrations of mundar peel extracts (5, 6, and 7% v/v) were examined by panelists using a hedonic test for their sensory qualities (color, aroma, taste, and mouthfeel). The result suggested that beverage with 6% mundar peel extracts was the most preferred formula. The total soluble content, pH, viscosity, and DPPH radical scavenging activity of this preferred formula were 2.98±0.05°Brix; 4.32±0.01; 4.93±0.16 cP, and 1025.78±8.39 AAE µg/mL, respectively.